Family Economic Transformation Strategy: Implementation of Financial Management in PKK Mothers of Bayah Sub-district - Wahyudi, Tri; Zulfikar, Rudi; Oktavianus, Afirman; Desmawan, Deris; Nofianti, Nana; Dwi Astuti, Kurniasi; Yuvisa Ibrani, Ewing (MOVE: Journal of Community Service and Engagement, 2024)
Family economic transformation in Bayah District, especially through the implementation of financial management by PKK mothers, is the focus of community service activities. Against the background of the need for financial literacy, especially among women, the main objective is to improve the understanding and skills of household financial management. The research methodology used a Participatory Action Approach involving 35 participants. Key outcomes significantly improved participants' financial literacy, from expenditure identification to financial priority evaluation. The implications of this service include the potential to improve family welfare and positive impacts on the community, especially through the active role of PKK mothers as agents of change in local economic development. Targeted financial management is key in improving financial literacy, contributing positively to economic growth in Bayah District. Although this dedication makes a significant contribution, it is recommended to involve more relevant parties, expand geographical coverage, and involve more societal elements to gain a more holistic understanding.